Bankers and Their Bonuses. (February 2014) - Bell, Brian; Van, John
<x xml:space="preserve">Abstract</x> We analyse the role of financial sector workers in the huge rise of the share of earnings going to those at the very top of the pay distribution in the UK. Rising bankers' bonuses accounted for two‐thirds of the increase in the share of the top 1% after 1999. Surprisingly, bankers' share of earnings showed no decline between the peak of the financial boom in 2007 and 2011, three years after the global crisis began. Nor did bankers' relative employment position deteriorate over this period. We discuss proposed policy responses such as transparency, bonus 'clawbacks', numerical bonus targets and tax.